A física do tunelamento quântico: uma proposta de organizador prévio para o ensino médio - Santos, Néviton Pereira (2017)
The present work shows a proposal of Didactic Sequence, composed of Previous Organizers as an instructional resource potentially facilitating Significant Learning, according to the Ausubel Theory. The Sequence begins with the survey of the Students' brainstorming, through the use of a Preliminary Organizer that brings to the surface the quantum tunneling phenomenon of water molecules trapped in beryllium structures, and continues making use of other specific organizers for each stage of the of wave phenomena present in elastic physical media of different densities. In the next step, we discussed the wave phenomena in electromagnetic waves through the Total Internal Reflection and Total Frustrated Total Reflection phenomena, expanding the concept of waves, with the objective of promoting the formation of subsunction concepts, and then the occurrence of Differentiation Progressive and Integrative Reconciliation of acquired concepts. The last stage of the didactic sequence was based on the detailed study of quantum phenomena from simple models, aiming at the phenomenon of Quantum Tunneling, through the use of PhET simulators "Quantum Tunneling" and "Double Well". The Teaching Sequence proposed here was applied to a class of third grade students from a public school system in the State of Bahia. The research is applied nature and descriptive-comprehensive objective, with the collection of information according to a qualitative approach. Preliminary results indicate that the methodology applied influenced students' learning. We sought to identify the argumentative changes of the participating students and what factors contributed most to the learning of the selected quantum concepts. The didactic material produced in this dissertation will be made available via digital media in the Polo Site 06 and in the MNPEF Site